Paraben exposure through drugs in the neonatal intensive care unit: a regional cohort study - Silvia Iacobelli; Silvia Iacobelli; Marie Commins; Simon Lorrain; Beatrice Gouyon; Duksha Ramful; Magali Richard; Anthony Grondin; Jean-Bernard Gouyon; Francesco Bonsante; Francesco Bonsante (Frontiers Media S.A., 2023)
Background and objectives: Environmental factors influence the development of very preterm infants (VPIs, born at less than 32 weeks of gestation). It is important to identify all potential sources of paraben exposure in these vulnerable infants. We aimed to quantify paraben exposure via drug administration in a cohort of VPI cared for in neonatal intensive care units (NICUs).Methods: A prospective, observational study was carried out over a five-year period in a regional setting (two NICUs using the same computerized order-entry system). The main outcome was exposure to paraben-containing drugs. The secondary outcomes were: time of the first exposure, daily intake, number of infants exceeding paraben acceptable daily intake (ADI: 0-10 mg/kg/d), duration of exposure, and cumulative dose.Results: The cohort consisted of 1,315 VPIs [BW 1129.9 (±360.4) g]. Among them, 85.5% were exposed to paraben-containing drugs. In 40.4% of infants, the first exposure occurred during the second week of life. Mean paraben intake and duration of exposure were, respectively, 2.2 (±1.4) mg/kg/d and 33.1 (±22.3) days. The cumulative paraben intake was 80.3 (±84.6) mg/kg. The ADI was exceeded in 3.5% of exposed infants. Lower GA was associated with higher intake and longer exposure (p < 0.0001). The main molecules involved in paraben exposure were: sodium iron feredetate, paracetamol, furosemide, and sodium bicarbonate + sodium alginate.Conclusion: Commonly used drugs are potential source of parabens, and ADI can be easily exceeded in VPIs cared for in NICUs. Efforts are needed to identify paraben-free alternative formulations for these vulnerable infants.